Chiapas, Latin America and the capitalist world-system - Aguirre Rojas, Carlos Antonio (Universidad Nacional de Quilmes, 2005)
This article is centered about the characterization of the universal and profound current meaning of the indigenous neozapatista movement in Chiapas for the antisystemic movements all over the world. Placed from a global, critical and ¿longue duree¿ perspective, the essay tries to reconstruct the worldwide impacts and the main political and social lessons of this Mexican neozapatismo.